The relationships between exchange rate and macroeconomic variables / Muhammad Firdauz Mohd Rasid - Mohd Rasid, Muhammad Firdauz (2012)
The topic of this research is the Exchange rate Volatility: the relationship between exchange rate and macroeconomic variable in Southeast Asia. This research investigates the relationship of macroeconomic variable that can be influence of exchange rate volatility in Southeast Asia. The for factor of macroeconomic are using to include in this study such as export GDP, inflation rate, base lending rate and foreign direct investment. There are 102 of data had gathered by 6 countries and 17 years (1995-2011). The researcher uses the Stata Software to process the data to find the result. The result of the study will indentify the hypotheses is accepted or rejected and the factor have significant or does not have significant with the exchange rate volatility in Southeast Asian.